Problem solving using manipulatives in elementary mathematics - Tabil, Rey D. (2006)
This study is a quasi-experimental research involving two approaches on teaching problem-solving in elementary mathematics. It sought to determine which of the two approaches, the manipulatives and conventional way of teaching, would have a better effect on achievement and retention of concepts taught. Twenty-four pairs from two Grade 6 classes were taught using lesson plans with the same instructional content but with different approaches. Other sources of data were the achievement test and delayed posttests, and a class observation. Observations revealed that students from the experimental group showed greater interest in classroom participation and manifested positive attitudes in learning mathematical concepts using the hands-on manipulatives.